Two and a Half Years Follow of the Pontic Site Development with Root Submergence Technique: A Case Report - Sah, SK (Journal of Nepalese Prosthodontic Society, 2022)
A soft tissue drape that is formed around the tooth, as it emerges from the bone, has both aesthetic and functional significance. Post-extraction soft and hard tissue changes are inevitable and it leads to a buccal concavity. The pontics for tooth or implant supported fixed partial denture in such cases appear longer. Preservation of a part of root preserves the periodontal apparatus and hence facilitates the optimal region for the pontic site development. This case report describes root submergence technique for pontic site development in maxillary anterior tooth-supported FPD with a follow up of two and a half years.